Clinical characteristics and outcomes in patients with Takayasu arteritis coexisting with myocardial ischemia and neurological symptoms: A multicenter, long-term, follow-up study - Huo, Junting; Wang, Bin; Yu, LiJun; Gao, Dewei; Cheng, Rui; Wang, Jiawei; Zhou, Xianliang; Tian, Tao; Gao, Linggen (Frontiers in Cardiovascular Medicine, 2022)
Background: The incidence of Takayasu arteritis (TA) patients coexisting myocardial ischemia and neurological symptoms is currently unknown. There is no standardized treatment algorithm in complex cases involving both coronary and intracranial arteries. Objective: To describe the clinical characteristics and outcomes in TA patients coexisting myocardial ischemia and neurological symptoms. Methods: We retrospectively collected and assessed the 1580 TA subjects and enrolled the patients with both neurological and myocardial ischemia symptoms from January 2002 to December 2021 in several hospitals. The incidence, clinical features, management strategy and prognosis of these patients was evaluated. Results: A total of 94 cases (5.9%,94/1580) were included in the present study. The imaging results showed that the subclavian arteries were the most frequently affected arteries. The most common stenosis site was the ostial and proximal segments of coronary, with 142 lesions in 94 cases (75.5%). Thirty-eight patients adopted interventional therapy, 21 subjects underwent surgical treatment, and the remaining 35 participants received conservative treatment. There were 20 (21.27%) late deaths during the mean follow-up period of 57.79 months. The mortality in the conservative treatment group was significantly higher than that of Interventional therapy and surgical treatment groups. Conclusions: It is not rare for patients with TA to involve both coronary and intracranial vessels. The stenosis and occlusion lesions most often involve the ostia and proximal segment of the arteries. Severe vascular lesions should be revascularized as soon as possible. Patients should be supplemented with glucocorticoids, antiplatelet, nitrates, statins and so on.